Integrated profiling of adiponectin and cytokine signaling pathways in high-fat diet-induced MASLD reveals early markers of disease progression - Rabia Johnson; Samukelisiwe Shabalala; Lawrence Mabasa; Liske Kotzé-Hörstmann; Nonhlakanipho Sangweni; Pritika Ramharack; Jyoti Sharma; Carmen Pheiffer; Afolake Arowolo; Hanél Sadie-Van Gijsen (Scientific Reports)
Abstract Metabolic dysfunction-associated steatotic liver disease (MASLD), which affects a significant portion of the global population, is linked to high-fat diets (HFD) and characterized by abnormal lipid accumulation and activation of inflammatory pathways in hepatocytes. The precise mechanisms underlying MASLD, especially the involvement of inflammatory cytokines in its pathophysiology, remain unclear. This study evaluated the changes and interactions of steatotic liver and inflammatory markers in an animal model of MASLD by feeding male Wistar rats a high-fat diet (HFD) for 17 weeks. After this period, the serum lipid profiles were assessed, along with liver enzymes, including aspartate aminotransferase (AST) and alanine aminotransferase (ALT). The changes in liver morphology and triglyceride levels were determined by histology and a colorimetric assay, respectively. Steatotic liver and inflammatory markers were measured using a RT2 ProfilerTMPCRArray and validated with quantitative real-time PCR (qRT-PCR). Histological evaluations indicated that HFD livers exhibited macrovesicular steatosis and lobular inflammation. The HFD-fed group had significantly higher hepatic triglyceride levels than the controls (383 ± 23 mg/dL vs. 100 ± 9 mg/dL) and elevated serum lipid levels (p < 0.0001), along with increased liver aminotransferase levels. Gene expression analysis showed decreased adiponectin signaling (AdipoR2, p < 0.001) and upregulated de novo lipogenesis (Srebf1, p < 0.05). Notably, pro-inflammatory cytokines (Cxcl10, Ccl2, Ilβ, p < 0.001; TNF-α, p < 0.01) were significantly elevated, correlating with reduced hepatic glucose transporter Glut2 expression (p < 0.05), as confirmed by STRING analysis. These findings demonstrate that HFD consumption alters key genes and pathways involved in adiponectin and insulin signalling, lipogenesis, and inflammatory responses, thereby contributing to the pathogenesis of MASLD. Additionally, it identifies a comprehensive chemokine expression profile, highlighting potential therapeutic targets for MASLD.